2022
DOI: 10.1016/j.eucr.2021.101904
|View full text |Cite
|
Sign up to set email alerts
|

Severe subcutaneous emphysema caused by small injury to the abdominal wall during robot-assisted laparoscopic radical prostatectomy

Abstract: A 67-year-old man underwent RARP in the Trendelenburg position with pneumoperitoneum at 12 mmHg. Gradual elevation of End-tidal CO2(EtCO2) began, and extensive subcutaneous emphysema was recognized when EtCO2 reached 58 mmHg. After interruption of pneumoperitoneum, careful observation of the surgical field led to detect an injury of the abdominal wall of 1 cm in length, suggesting the cause of severe subcutaneous emphysema. The injury was repaired and RARP was terminated without any cardiovascular problems. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…McAllister et al [13] reported that the 24-hour postoperative computed tomography scans of patients who underwent laparoscopic cholecystectomy revealed grossly undetectable but clinical SE in 56% of cases. Similarly, Worrell, Saggar, and colleagues recognized SE in up to 99% of all laparoscopic cases based on radiographic ndings and computed tomography scans [1,9,[13][14][15][16]]. The reported life-threatening complications and high incidence of clinically relevant SE (21%), including two abdominal infections caused by SE in our study, indicate that this complication deserves immediate consideration [1][2][3][4][5][6].…”
Section: Discussionsupporting
confidence: 65%
“…McAllister et al [13] reported that the 24-hour postoperative computed tomography scans of patients who underwent laparoscopic cholecystectomy revealed grossly undetectable but clinical SE in 56% of cases. Similarly, Worrell, Saggar, and colleagues recognized SE in up to 99% of all laparoscopic cases based on radiographic ndings and computed tomography scans [1,9,[13][14][15][16]]. The reported life-threatening complications and high incidence of clinically relevant SE (21%), including two abdominal infections caused by SE in our study, indicate that this complication deserves immediate consideration [1][2][3][4][5][6].…”
Section: Discussionsupporting
confidence: 65%
“…3 4 Micturition disturbance has been described in children with ADEM, but isolated urinary retention as an initial manifestation is extremely rare. 5…”
Section: Discussionmentioning
confidence: 99%
“…1 Fukui et al from Japan described an 11-year-old boy presenting with acute urinary retention, fever, headache, and weakness of the extremities with MRI findings suggestive of ADEM. 5 Within 7 days of steroid initiation therapy, the child could void urine normally. Improvement of lesions on MRI was observed on day 14 of admission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations